Implementing Fractal to Define Balinese Traditional Architectural Facade Beauty: The Kori Agung - Khansa Salma Aisyah; Vincentius Totok Noerwasito; Didit Novianto (DIMENSI (Journal of Architecture and Built Environment), 2023)
Fractals have been theoretically used to explain visual beauty from the urban scale to the context of architectural facades. How we perceive the visual beauty of architecture is likely dependent on subjectivity. However, the fractal is applicable for defining visual beauty and as a quantifiable method that provides objectivity for analysis. Previous research has used fractals, particularly in facades, to determine the beauty in complex geometry and quantify the complexity. However, the application of fractals in traditional architecture remains to be explored. Therefore, this article will discuss in detail how fractal is a suitable method to study the visual beauty of traditional architectural facades using fractal geometry and fractal dimension index. The case used to illustrate the implementation is Kori Agung of Balinese traditional architecture, known for its grandeur and luxurious facade images. It embodies the visual beauty of its facade due to its textured, layered, and complex visual appearance.